IMPROVING THE COMPETITIVENESS OF THE REGION: CLUSTER APPROACH - A. Kamalova (Вестник университета, 2016)
The article covers some conceptual approaches and best practices of implementing the cluster polices in practice to stimulate success and competitiveness.